2017
DOI: 10.1111/azo.12224
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterisation of the digestive tract of the catfish Lophiosilurus alexandri Steindachner, 1876 (Siluriformes, Pseudopimelodidae)

Abstract: The anatomical arrangement of the digestive tract and the length (cm) of the oesophagus and intestine of the catfish Lophiosilurus alexandri were described, and the intestinal coefficient was determined. L. alexandri oesophagus is short, in median position, and presents longitudinally folded mucosa, whilst its epithelium is stratified and non-keratinised, with mucous, claviform and epithelial cells. Stomach has "C" shape, with folded mucosa along cardiac region, disordered in the fundic region, and directed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
2
17
0
1
Order By: Relevance
“…In our study, EC CCK-8+ concentrated more in the first midgut segment of the hybrid catfish (C1). Similar to the hybrid cattish, a higher density of CCK cells/expression in the first midgut segment, closer to stomach pyloric, was also found in 5 from the 9 carnivorous species such as G. morhua (Mello et al, 2017), R. giurinus. (Hur et al, 2016), S. ocellatus (Webb et al, 2010), S. quinqueradiata (Murashita et al, 2006), S.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In our study, EC CCK-8+ concentrated more in the first midgut segment of the hybrid catfish (C1). Similar to the hybrid cattish, a higher density of CCK cells/expression in the first midgut segment, closer to stomach pyloric, was also found in 5 from the 9 carnivorous species such as G. morhua (Mello et al, 2017), R. giurinus. (Hur et al, 2016), S. ocellatus (Webb et al, 2010), S. quinqueradiata (Murashita et al, 2006), S.…”
Section: Discussionmentioning
confidence: 53%
“…undecimalis (Machado et al, 2013), H. platyrhynchos (Faccioli et al, 2014), H. hippoglossus (Murray et al, 1996), L. calcarifer (Purushothaman et al, 2016), P. americanus and P. ferruginea (Murray et al, 1996), L. alexandri (Mello et al, 2017), S. geneionema (Hur et al, 2016), and A. anguilla (Domeneghini et al, 2005). Differently from hybrid catfish, D. dentex (Carrassón et al, 2006) and O. mykiss (Marchetti et al, 2006) showed similar cell distribution with each other.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The serosa layer constitutes both connective tissue and mesothelium (Figure 4c). The short oesophagus shows longitudinal folds that allow great distensibility to facilitate the passage of large food, like fish (Faccioli et al, 2014;Mello et al, 2019;Rodrigues & Cargnin-Ferreira, 2017;Vidal et al, 2020). Oesophageal epithelium of studied species is composed of epithelial cells, goblet cells and club cells.…”
Section: Resultsmentioning
confidence: 99%
“…Catfish is one of the freshwater teleost fish that live near to the bottom. It is an omnivorous type that has a convoluted tubular gastrointestinal tract (short oesophagus, stomach and followed by intestine) and is known as stomach teleost (Lee et al, 2001;Moawad et al, 2017;Mello et al, 2019). In fish, it has been reported that the alimentary pattern could affect hormonal secretion (Navarro et al, 2002).…”
Section: Discussionmentioning
confidence: 99%